2016
DOI: 10.21303/2461-4262.2016.00212
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Batch Intensive Quenching Processes When Using Hydrodynamic Emitters in Quench Tanks

Abstract: The paper discusses patented in Ukraine a new intensive quenching IQ–2 technology based on film boiling resonance effect [1]. Namely, the paper discusses improving of the batch intensive quenching (IQ) process known as IQ-2 method by the use of hydrodynamic emitters installed in quench tanks. The hydrodynamic emitters produce oscillating waves in the quench media with the frequency of the film boiling process creating a resonance effect. Two- and three-step IQ-2 processes are considered. Specifics of the heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…At this stage, a good correlation between the temperature and displacement fields could be observed, indicating that the shrinking of the block was driven by thermal stresses. T. Lübben, et al (2014) reported that the temperature difference ΔT = (Tmax -Tmin) between the coldest and hottest zones could be correlated to the intensity of thermal stresses [48,49]. Results reported in Figure 13 also reveal that due to high heat removal, the edges were the first elements to experience Ms temperature [19,23] and build a rigid frame composed of hard martensitic layers.…”
Section: Distortion Evolution During Quenchmentioning
confidence: 95%
“…At this stage, a good correlation between the temperature and displacement fields could be observed, indicating that the shrinking of the block was driven by thermal stresses. T. Lübben, et al (2014) reported that the temperature difference ΔT = (Tmax -Tmin) between the coldest and hottest zones could be correlated to the intensity of thermal stresses [48,49]. Results reported in Figure 13 also reveal that due to high heat removal, the edges were the first elements to experience Ms temperature [19,23] and build a rigid frame composed of hard martensitic layers.…”
Section: Distortion Evolution During Quenchmentioning
confidence: 95%
“…As a result, customizers face some problems connected with distortion issues because in many cases cooling should be interrupted at proper time to prevent non-uniformity of cooling during quenching as shown Fig. 6 [16,17]. A methodology is developed for testing liquid media as a quenchant and results of testing can be successfully used for recipes development.…”
Section: Discussionmentioning
confidence: 99%